THE EFFECT OF THE USE OF DIGITAL MARKETING AND THE EASE OF ACCESS OF ONLINE SHOPPING APPLICATION SERVICES IN IMPROVING PURCHASING POWER OF THE COMMUNITY OF THE MEDAN CITY IN THE ERA REVOLUTION OF THE MARKETING INDUSTRY 4.0 - Herosian, Mila Yulia; Samvara, Made Adhiguna (Jurnal Ilmiah Bina Manajemen, 2020)
The use of data services is not new in the midst of the community because all levels of society can already use online-based services. This is supported by the presence of online shopping applications such as Lazada, Shopee, Tokopedia, Elevenia, Bukalapak, Blibli.com, OLX, Mataharimall.com, and DJ.ID. This research is based on the theory of Marketing Management science related to the development of the digital economy in modern global-based platform organizations as one of the applications that accelerates and facilitates the use of online shopping application services in Indonesia. This research method uses a quantitative descriptive approach with the nature of the research is explanatory. The population in this study is the number of digital marketing service users by 120,856 respondents and the sampling technique using the Slovin formula obtained as many as 100 respondents used in this study. The results obtained in this study are that partially the use of digital marketing obtained tcount > ttable (1,588 > 1,290) and easy access to services obtained tcount > ttable (1,434 > 1,290) has a significant positive effect > 0.10 in increasing people's purchasing power Medan city, while simultaneous use of digital marketing and the ease of access of services obtained the value of Fcount> Ftable (2.337 > 2.36) has a positive and not significant effect on increasing the purchasing power of the people of Medan City in the era of the marketing industry revolution 4.0 Penggunaan layanan data bukan menjadi hal yang baru di tengah lingkungan masyarakat karena semua lapisan masyarakat sudah dapat menggunakan layanan berbasis online. Hal tersebut didukung dengan adanya aplikasi belanja online seperti Lazada, Shopee, Tokopedia, Elevenia, Bukalapak, Blibli.com, OLX, Mataharimall.com, dan DJ.ID. Penelitian ini didasarkan pada teori ilmu Manajemen Pemasaran terkait dengan perkembangan ekonomi digital dalam organisasi modern berbasis global platform sebagai salah satu aplikasi yang mempercepat dan mempermudah penggunaan layanan aplikasi belanja online di Indonesia. Metode penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan sifat penelitian yaitu explanatory. Populasi dalam penelitian ini adalah jumlah pengguna layanan digital marketing sebesar 120.856 orang responden dan teknik pengambilan sampel dengan menggunakan rumus slovin diperoleh sebanyak 100 orang responden digunakan dalam penelitian ini. Hasil yang diperoleh dalam penelitian ini adalah bahwa secara parsial penggunaan digital marketing diperoleh nilai thitung > ttabel (1,588 > 1,290) dan kemudahan akses layanan diperoleh nilai thitung > ttabel (1,434 > 1,290) berpengaruh positif dengan signifikan > 0,10 dalam meningkatkan daya beli masyarakat kota Medan, sedangkan secara simultan penggunaan digital marketing dan kemudahan akses layanan diperoleh nilai Fhitung > Ftabel (2,373 > 2,36) berpengaruh positif dan tidak signifikan dalam meningkatkan daya beli masyarakat Kota Medan di era revolusi industri marketing 4.0